QUEUE, with Poisson arrivals, constant service time and infinite servers, BUSY PERIOD DISTRIBUTION - Ferreira, M. A. M. (arXiv:2109.10882, 2025)
The queue system,with Poisson arrivals,constant service time and infinite servers, busy period distribution is intensively studied because, due to its probability density function quite easy interpretation, it may serve as a clue to interpret the queue systems, with Poisson arrivals, infinite servers, and other service time distributions, busy period distributions. In this work the queue system, with Poisson arrivals,constant service time and infinite servers, busy period distribution parameters are exactly computed and its probability density function is interpreted and explained. The only problem is how to compute the distribution function, for which an algorithm is presented and exemplified its application.